Analysis of strength degradation of coal and rock masses and stability of mined areas under long term immersion environment - Wu Zuoqi; Han Keming; Zhou Ni; Zheng Zhiyong; Liu Jiashun (PLoS ONE, 2026)
To address the stability challenges of suspended roof goaf and engineering disasters in coal mine goafs under long-term water immersion, coal rock mass was selected as the research object. Triaxial compression tests under seepage-stress coupling were conducted to analyze the strength degradation and permeability evolution of coal rock mass. Based on the bearing characteristics of coal pillars in suspended roof goaf, a critical criterion for instability of room pillar suspended roof goaf was established, then the numerical simulation studies were conducted using UDEC 7.0 to investigate the influence of different mining parameters and occurrence conditions on the stability of goaf. The research results show that: (1) When the seepage pressure is constant, as the confining pressure increases, the peak stress of the coal samples increases gradually, while the permeability coefficient gradually decreases; when the confining pressure is constant, as the seepage pressure increases, the peak stress gradually decreases, while the permeability coefficient increases gradually. (2) When the stability safety factor of the coal pillar is lower than 1.5, the coal pillar will not be able to maintain long-term stability and corresponding reinforcement measures need to be taken. (3) The increase of occurrence depth will lead to the increase of coal pillar deformation, but as long as the ratio of mining and remaining is moderate, the coal pillar can support the overlying strata and maintain stability; (4) The increase in ratio of mining and remaining strengthens the supporting effect of coal pillars, which helps to improve the stability of the roof, reduce the subsidence of the rock strata above the goaf, and lower the risk of roof collapse. The research results can provide technical references for the prevention and control of hanging roof disasters in mines with similar coal mining processes.